2013
DOI: 10.2478/prolas-2013-0076
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Oxalate and Some Inorganic Anions in Green and Black Tea

Abstract: Oxalate concentration differs in various daily consumed food products. The role of oxalic acid in the human body is very significant, as its compounds are responsible for the stability of biological membranes. However, insoluble calcium and magnesium oxalates can be accumulated in the body in the form of kidney stones. Oxalate concentration has been measured by high performance liquid, gas after derivatization and ion chromatography (IC). The most effective method for the simultaneous determination of oxalate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
(3 reference statements)
1
5
0
Order By: Relevance
“…On the other hand, the migration time value for nitrite ion in our study was in agreement with the work reported in literature [28,32]. Generally the nitrate content as shown in Table 4 for all the tea samples obtained in this study were found to be lower than the values reported by [22] and [34] in various tea samples studied. For the tea samples with nitrate content above the average daily intake limit recommended by WHO, it is recommended that measures should be put in place in the regions were these teas are grown in order reduce high usage of fertilizers.…”
Section: Nitrate Nitrite and Bromate Ions Determination In Tea Samplessupporting
confidence: 92%
“…On the other hand, the migration time value for nitrite ion in our study was in agreement with the work reported in literature [28,32]. Generally the nitrate content as shown in Table 4 for all the tea samples obtained in this study were found to be lower than the values reported by [22] and [34] in various tea samples studied. For the tea samples with nitrate content above the average daily intake limit recommended by WHO, it is recommended that measures should be put in place in the regions were these teas are grown in order reduce high usage of fertilizers.…”
Section: Nitrate Nitrite and Bromate Ions Determination In Tea Samplessupporting
confidence: 92%
“…Considering ion exchange columns, one of the most referenced columns is IonPac AS4A [1,59,60,[62][63][64]72]. Other authors have used different ones: propylamine anion exchange column (25 cm × 4.6 mm; 6 µm particle size), diethylaminoethyl (DEAE) anion exchange column (250 × 4.6 mm; 5 µm particle size), and Hamilton HA-X8.00 column with strong anion exchange resin in the sulfate form (255 × 5 mm; 7-10 µm particle size) [84]; Alltech All-Sep anion exchange column (100 × 4.6 mm; 7 µm particle size) [17] and Shodex IC SI-90 anion exchange column (250 × 4 mm; 9 µm particle size) filled with KanK-ASt (120 × 5 mm, 14 µm particle size) [71]. For ion exclusion, it seems that an ion exclusion column (300 × 7.8 mm) is frequently the selected one, either from Bio-Rad [32,34,40,61,70] or Rezex [65][66][67][68] brands.…”
Section: Hplc Conditionsmentioning
confidence: 99%
“…These columns are chosen considering different separation modes of HPLC. Ion chromatography is an effective method for the determination of oxalate ions because oxalic acid is a strong acid, giving away its protons and becoming negatively charged [71].…”
Section: Hplc Conditionsmentioning
confidence: 99%
See 2 more Smart Citations